Context, Service Provision, and Reflections on Future Directions of Support for Individuals With Intellectual Disability in Singapore. Issue 2 (June 2015) - Poon, Kenneth K.
Abstract The author examined how individuals with intellectual disability (ID) are supported in Singapore and what are the needs for further service development. Service provision for individuals with disabilities in Singapore is broadly reflective of its changing needs as a developing nation. Disability service provision began in the pre‐World War II period and then advanced greatly during the last 20 years with the proliferation of early intervention and specialized programs for school‐aged children as well an expansion of adult‐focused supports. Social services are organized along the "Three Ps Model" (public, private, and people), involving a collaboration of nongovernmental organizations, the government, and the corporate sector. With respect to school‐age services, although a fairly comprehensive system has been put in place to support the education of students with disabilities, the system continues to evolve. The situation is more limited with respect to supports for adults. With Singapore reaching high levels of employment, there is an impetus for some individuals with ID to be part of the workforce; for those without work skills, day options for some include workshops and developmental activity centers. For parent carers, supports remain limited and there is a disparity between the goals outlined in the World Disability Report and currently available options for most adults and their families. Recommendations include studies to better understand the population of persons with ID and their needs, a reexamination of the diffused responsibility for disability‐related services within the government, and an evaluation of the way services are delivered by the voluntary sector.